Parametrização do transporte de energia cinética turbulenta na camada limite convectiva - Puhales, Franciano Scremin (2011)
In this work a parameterization for the transport terms of the turbulent kinetic energy (TKE) budget equation, valid for a convective boundary layer (CBL) is presented. This is a hard task to acomplish from experimental data, especially because of the difficulty associated to the measurements of pressure turbulent fluctuations, which are necessary to determine the pressure correlation TKE transport term. Thus, employing a large eddy symulation (LES), all terms of the TKE budget equation were determined for a CBL. From these data, polynomials that describe the TKE transport terms vertical profiles were adjusted for a CBL. The found polynomial fits are a good description of the LES data, and from them it is shown that a simple formulation that directly relates the transport terms to the TKE magnitude has advantages on other parameterizations commonly used in CBL numerical models. Furthermore, the present study shows that the TKE turbulent transport term dominates over the TKE transport by pressure perturbations and that for most of the CBL these two terms have apposite signs. The simulation consists of a full diurnal PBL cycle utilizing, at the surface, a forcing obtained from experimental data, so that the numerical experiment represents a more realistic case than a idealized CBL.